Kak nam obustroit' Rossiiu . Kak nam obustroit' Rossiiu . How Can We Improve Russia . Как нам обустроить Россию - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Discussion about interrelation of the powers of the President, the Government and the Parliament in Russia. Contributors: Dolgov, Georgii (Anchor) Дискуссия о соотношении власти президента, правительства и парламента в России. Создатели: Долгов, Георгий (Ведущий/Ведущая)